Coal Supply Sustainability in China: A New Comprehensive Evaluation Methodology - Li, Pin; Yu, Hongyuan; Zhang, Jinsuo; Du, Meiyang; Xiong, Jing (Frontiers in Energy Research, 2021)
Coal is a major source of energy in China. Quantifying China’s coal supply sustainability is essential to track China’s efforts towards sustainable development and achieve carbon neutrality goals. In this research, in addition to availability, economic sustainability, environmental sustainability and technological sustainability, we specially considered health and security, and transport sustainability of China’s coal supply. We select 19 indicators from the above six dimensions to build a coal supply sustainability index and construct a novel optimized comprehensive evaluation model with level difference maximization to evaluate China’s coal supply sustainability. The results showed that the policies issued by the Chinese government have effectively improved coal supply sustainability. China’s coal supply sustainability level has improved significantly, with the figure nearly doubling from 0.338 in 2000 to 0.7004 in 2019. To improve the sustainability of China’s coal supply further fundamentally, it is still necessary to improve energy diversification. Since phasing out China’s coal reliance requires considerable time, the Chinese government needs to introduce more positive and effective policies to such as increase the research and development support for carbon capture, utilization and storage technology, etc. to improve the sustainability of coal supply. The results of this research presented in this paper will have reference value for both promoting the sustainable development of China and other coal-consuming countries in the world.